ANALYSIS OF APPLYING SONG MEDIA IN ENGLISH LEARNING OF ELEMENTARY SCHOOL AT THIRD GRADE STUDENTS IN SDN CIBEBER 1 CIMAHI - Herliana, Wina; Daniawati, Eka Deti (IKIP Siliwangi, 2018)
In the learning of English language at school there are many ways can be done by teachers, including in using of tools or props and media can be appropriate to the level and level of education available. For learning English at level of basic education there are a number of learning that can be used as alternatives, one of which is the song media. This article discussed about steps of implementation song media of elementary school at Cibeber 1 Cimahi. Analysis of the problems used as research materials using descriptive qualitative analysis, while the focus of the object of observation is the steps of media song implementation in the school mention above. From the result of observation and analysis conducted by the autors, it is known that there is still incompatibility in the steps of media song. Implementation conducted by teacher with the steps implementation of instructional media as recommended by the experts of English education, especially experts who deepen the problem of media implementation song in learning English at school.